The influence of the Brazil and Malvinas Currents on the Southwestern Atlantic Shelf Circulation - Matano, Ricardo (2010)
The oceanic circulation over the southwestern Atlantic shelf is influenced by large tidal amplitudes, substantial freshwater discharges, high wind speeds and – most importantly – by its proximity to two of the largest western boundary currents of the world ocean: the Brazil and Malvinas currents. This review article aims to discriminate the dynamical processes controlling the interaction between this extensive shelf region and the deep-ocean. The discussion is focused on two broad regions: the South Brazil Bight to the north, and Patagonia to the south. The exchanges between the Brazil Current and the South Brazil Bight are characterized by the intermittent development of eddies and meanders of the Brazil Current at the shelfbreak. However, it is argued that this is not the only – nor the most important – influence of the Brazil Current on the shelf. Numerical simulations show that the thermohaline structure of the South Brazil Bight can be entirely ascribed to steady state, bottom boundary layer interactions between the shelf and the Brazil Current. The Malvinas Current does not show the development of eddies and meanders, but its influence on the Patagonian shelf is not less important. Models and observations indicate that the Malvinas Current not only controls the shelfbreak dynamics and cross-shelf exchanges but also influences the circulation in the shelf's interior.